What’s so critical about Critical Neuroscience? Rethinking experiment, enacting critique - Fitzgerald, Des; Matusall, Svenja; Skewes, Joshua; Roepstorff, Andreas (Frontiers in Human Neuroscience, 2014)
In the midst of on-going hype about the power and potency of the new brain sciences, scholars within ‘Critical Neuroscience’ have called for a more nuanced and sceptical neuroscientific knowledge-practice. Drawing especially on the Frankfurt School, they urge neuroscientists towards a more critical approach – one that re-inscribes the objects and practices of neuroscientific knowledge within webs of social, cultural, historical and political-economic contingency. This paper is an attempt to open up the black-box of ‘critique’ within Critical Neuroscience itself. Specifically, we argue that limiting enactments of critique to the invocation of context misses the force of what a highly-stylized and tightly-bound neuroscientific experiment can actually do. We show that, within the neuroscientific experiment itself, the world-excluding and context-denying ‘rules of the game’ may also enact critique, in novel and surprising forms, while remaining formally independent of the workings of society, and culture, and history. To demonstrate this possibility, we analyze the Optimally Interacting Minds paradigm, a neuroscientific experiment that used classical psychophysical methods to show that, in some situations, people worked better as a collective, and not as individuals – a claim that works precisely against reactionary tendencies that prioritise individual over collective agency, but that was generated and legitimized entirely within the formal, context-denying conventions of neuroscientific experimentation. At the heart of this paper is a claim that it was precisely the rigours and rules of the experimental game that allowed these scientists to enact some surprisingly critical, and even radical, gestures. We conclude by suggesting that, in the midst of large-scale neuroscientific initiatives, it may be 'experiment,' and not 'context,' that forms the meeting-ground between neuro-biological and socio-political research practices.